Penerapan Asas Legalitas dalam Kasus Pelanggaran Hak Asasi Manusia yang Dilakukan oleh KKB (Kelompok Kriminal Bersenjata) di Papua - August Hamonangan; Herliyant Marsal Anugrah; Hamzah Robbani (Decisio: Jurnal Ilmiah Hukum, 2024)
The era of globalization brings numerous challenges to human rights violations worldwide, including in Indonesia. The human rights issue in Papua, known for its rich natural resources and cultural diversity, has become a controversial topic. Papua faces various problems, including friction between indigenous communities and non-Papuan immigrants, disinformation campaigns, and reports of human rights violations by the Indonesian security forces. Factors adding to the complexity of the situation in Papua include its colonial background, local power dynamics, and advancements in communication technology. The principle of legality plays a crucial role in this context, ensuring every government action is based on existing laws. This qualitative research explores the application of the legality principle concerning human rights violations by the Armed Criminal Group (KKB) in Papua, focusing on the protection of human rights for Papuans. The research results show that the legality principle emphasizes the importance of government actions being based on existing laws and the need for consistent application of laws that do not conflict with human rights. The conflict in Papua requires a holistic solution approach, considering political, social, and cultural elements and strengthening education about human rights and the development of social infrastructure.